STUDI EKSPLANATORI-KONFIRMATORI KEHIDUPAN KRISTEN BERDASARKAN LUKAS 16:19-31 DI KALANGAN HAMBA TUHAN SE-KABUPATEN JEMBER JAWA TIMUR - Soehadi Widjaja; Paulus Sentot Purwoko; Daniel Suharto; Timotius Sukarna (Sekolah Tinggi Teologi Duta Panisal, 2021)
The number of theologies that breathe success appears among God's servants throughout Jember district, which are alleged to have deviated from the biblical Christian life. This encourages this research to be carried out. The aim is to find out how much the level of application, dimensions and background categories that tend to influence the implementation of Christian life based on Luke 16: 19-31 among the servants of God in Jember Regency, East Java. The method used is the quantitative method in the form of explanatory-confirmatory studies of the text of Luke 16: 19-31 and literature studies related to the topic of Christian life as well as examining moderate variables in the form of categories of the background of the object of research. As a result, first, the level of implementation of Christian life based on Luke 16: 19-31 among God's servants throughout Jember district is in the